2020
DOI: 10.1007/s10570-020-03430-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cellulose-rich membranes from wood: effect of wood pretreatment process on membrane performance

Abstract: In this study cellulose-rich membranes were fabricated from untreated and treated hardwood biomass solutions in 1-ethyl-3-methylimidazolium acetate ([Emim][OAc])—dimetylsulfoxide (DMSO) system via wet phase separation. Wood treatment methods aimed to get purified cellulose fraction of wood. Treatment sequence was as followed: deep eutectic solvent pretreatment, sodium chlorite bleaching, and alkaline treatment. Resulted biomass after each treatment step was characterized by chemical composition and crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Cellulose Acetate has also been recovered from waste cigarette filters which is one of the most abundant forms of plastic waste present globally. Typically, biomass has 40 to 60 % cellulose, 15 to 30 % hemicellulose, and 10 to 25 % lignin [8] . From Figure 3 it can be confirmed that cellulose has hydroxyl groups, which are responsible for its high hydrophilicity.…”
Section: Types Of Biopolymers For Membrane Productionmentioning
confidence: 90%
See 3 more Smart Citations
“…Cellulose Acetate has also been recovered from waste cigarette filters which is one of the most abundant forms of plastic waste present globally. Typically, biomass has 40 to 60 % cellulose, 15 to 30 % hemicellulose, and 10 to 25 % lignin [8] . From Figure 3 it can be confirmed that cellulose has hydroxyl groups, which are responsible for its high hydrophilicity.…”
Section: Types Of Biopolymers For Membrane Productionmentioning
confidence: 90%
“…The properties of lignin and the complexity of the chemical composition of the wood prevented the formation of a dense top layer. [8] After the removal of lignin and hemicellulose, the wood membrane becomes flexible, with greater hydrophilicity and oleophobicity. [10] With further treatments, the purity of cellulose increased producing a chemically more homogeneous, tighter membrane having increased retention and decreased permeance.…”
Section: Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…Despite the chosen method of describing cellulose as a polymer-regardless of whether it is recognised as hydrophilic or an amphiphilic one [5][6][7][8][9]-the regenerated cellulose membranes are universally acknowledged as very hydrophilic, having higher biocompatibility and lower fouling tendency when compared with petroleum-based polymers due to cellulose being a biopolymer [10][11][12][13]. The existing research focusing on the manufacturing of cellulose membranes is highly variable regarding whether research groups prefer to use commercially produced cellulose [14][15][16] or biobased cellulose sources [2,17,18], using various solvents with high capacity for cellulose dissolution [3,4,19]. The steady interest towards ionic liquids (ILs) as cellulose and biomass solvent media is supported with such characteristics as their potential recyclability, low vapour pressure, and good chemical and thermal stability [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%